2020
DOI: 10.1371/journal.pone.0236039
|View full text |Cite
|
Sign up to set email alerts
|

Distinct patterns of brain Fos expression in Carioca High- and Low-conditioned Freezing Rats

Abstract: Background The bidirectional selection of high and low anxiety-like behavior is a valuable tool for understanding the neurocircuits that are responsible for anxiety disorders. Our group developed two breeding lines of rats, known as Carioca High-and Low-conditioned Freezing (CHF and CLF), based on defensive freezing in the contextual fear conditioning paradigm. A random selected line was employed as a control (CTL) comparison group for both CHF and CLF lines of animals. The present study performed Fos immunoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 108 publications
0
8
0
Order By: Relevance
“…Finally, other studies developed by our group but not discussed in the scope of this review (for details, see Dias et al, 2014 ; Lages et al, 2023 ; Léon et al, 2020 ) also indicate functional and structural changes in neural circuits underlying anxiety in the CHF rat line, which seems to indicate that the phenotyping process that strengthened this trait anxiety was also expressed in terms of a great capacity for neural plasticity.…”
Section: Chf Rat Line As a Model Of Gadmentioning
confidence: 56%
“…Finally, other studies developed by our group but not discussed in the scope of this review (for details, see Dias et al, 2014 ; Lages et al, 2023 ; Léon et al, 2020 ) also indicate functional and structural changes in neural circuits underlying anxiety in the CHF rat line, which seems to indicate that the phenotyping process that strengthened this trait anxiety was also expressed in terms of a great capacity for neural plasticity.…”
Section: Chf Rat Line As a Model Of Gadmentioning
confidence: 56%
“…Our data revealed that treatment of CBD produced different effects on neuropathic pain in individuals with distinct anxiety levels (CLF, CTL, CHF lineages). The lineages did not show basal differences, confirming that nociceptive stimuli did not select these lineages [ 36 , 42 ]. Moreover, a lower efficacy of CBD was observed in the CHF+CCI group compared to the CTL+CCI in mechanical and cold thermal sensitivity, which suggests the hypothesis of an elevated level of sensitivity in this lineage.…”
Section: Discussionmentioning
confidence: 87%
“…Their Table 1 maps CHF rats to human generalized anxiety in terms of (their words): 1) High and diffuse anxiety in contextual fear conditioning, elevated plus maze, and avoidance behavior in the elevated T-maze; 2) Immobility/freezing behavior; 3) Different pattern of acquisition/extinction in response to context and cue; 4) Increased corticosterone serum levels; 5) Benzodiazepine and serotonergic anxiolytics attenuate freezing behavior in CHF but not CLF rats; and 6) Higher alcohol intake. CHF rats have also shown parallel changes in the function and structure of neural circuits thought to underlie anxiety (Dias et al, 2014 ; Lages et al, 2023 ; León et al, 2020 ).…”
Section: Strain Derivation – Personality In Ratsmentioning
confidence: 99%